PENGARUH PERILAKU BERBAGI PENGETAHUAN (KNOWLEDGE SHARING) DAN KOMPETENSI TERHADAP KINERJA KARYAWAN PT. POS AMBON - Wairisal, P. L.; Prajawati, Maretha Ika (IQTISHODUNA, 2017)
Abstract: The effectiveness of any organization including the business organization / company dependsdirectly on the effectiveness of the human resources work of the organization concerned. Human resourcedevelopment that focuses on the development of employee knowledge or knowledge resources is an importantrequirement for the company in exploring human resource capability to achieve company goals. Currentlyawareness of the importance of knowledge resources (knowledge) as the company’s intellectual capital toachieve competitive advantage is higher. Knowledge plays a very important role in the progress of thecompany. The purpose of this research is to analyze and explain the influence of knowledge sharing onperformance, competence to performance, and knowledge sharing and competence on performance at PT PosKota Ambon.